(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides for the study of the typology and system of exercises used in teaching foreign languages, the identification of modern requirements for them, and the analysis of the methodological foundations for the formation of an effective system of exercises. The article uses methods of historical-comparative analysis, systematic approach and contextual analysis. Theoretical sources on typologies and systems of exercises developed in different periods have been studied, a comparative analysis of which has been carried out. As a result of the study, various typologists of exercises (language and speech exercises, prescription and reproductive exercises, complex language exercises, etc.) were identified and analyzed. The basic requirements for the exercise system are established: the development of cognitive processes, the inclusion of all linguistic aspects and types of speech activity, the growing level of difficulty, interdependence, repeatability and communicative orientation. Also, the importance of exercises and the requirements for them have been determined in the methodology of Modern Language Teaching. Exercises are considered the basis of the process of teaching a foreign language, the formation and application of which depends on a number of factors. An effective exercise system should be aimed at the balanced development of cognitive, linguistic and communicative aspects. A system of exercises developed on the basis of modern approaches makes it possible to effectively formulate communicative competence of language learners.